Smart Nanocarriers for the Targeted Delivery of Therapeutic Nucleic Acid for Cancer Immunotherapy - Abu Baker; Jochen Lorch; David VanderWeele; Bin Zhang (MDPI AG, 2023)
A wide variety of therapeutic approaches and technologies for delivering therapeutic agents have been investigated for treating cancer. Recently, immunotherapy has achieved success in cancer treatment. Successful clinical results of immunotherapeutic approaches for cancer treatment were led by antibodies targeting immune checkpoints, and many have advanced through clinical trials and obtained FDA approval. A major opportunity remains for the development of nucleic acid technology for cancer immunotherapy in the form of cancer vaccines, adoptive T-cell therapies, and gene regulation. However, these therapeutic approaches face many challenges related to their delivery to target cells, including their in vivo decay, the limited uptake by target cells, the requirements for nuclear penetration (in some cases), and the damage caused to healthy cells. These barriers can be avoided and resolved by utilizing advanced smart nanocarriers (e.g., lipids, polymers, spherical nucleic acids, metallic nanoparticles) that enable the efficient and selective delivery of nucleic acids to the target cells and/or tissues. Here, we review studies that have developed nanoparticle-mediated cancer immunotherapy as a technology for cancer patients. Moreover, we also investigate the crosstalk between the function of nucleic acid therapeutics in cancer immunotherapy, and we discuss how nanoparticles can be functionalized and designed to target the delivery and thus improve the efficacy, toxicity, and stability of these therapeutics.